Investigations for the application of EPB shields in difficult grounds / Untersuchungen für den Einsatz von Erddruckschilden in schwierigem Baugrund. Issue 1 (February 2014) - Galli, Mario; Thewes, Markus
Abstract As a result of growing urbanisation, subsurface space is developed and has to be expanded. New and bigger tunnels are required to meet the infrastructural needs. The ground is the decisive factor regarding the type of tunnelling method and its efficiency. The bigger such projects the greater the chance to encounter inhomogeneous in situ ground conditions. This makes an adequate and economic choice of the process technology more difficult, especially in mechanised shield tunnelling. A clear differentiation based on the grain‐size distribution between the field of application of an EPB shield and a hydro shield nowadays is hardly possible. An application of a hydro shield machine in fine soils is just as feasible as tunnelling with EPB shields in coarse soils. In this article, the authors explain selected geological conditions, which represent challenging situations for the application of EPB shields. Therefore, it is particularly focused on overconsolidated cohesive soils, highly permeable non‐cohesive soils and sedimentary rock as well as areas of mixed face conditions (rock and soil). Moreover, test methods and tools for the planning and the construction phase are presented. Im Zuge der fortschreitenden Urbanisierung wird der Bau neuer und größerer Tunnel erforderlich. Je größer solche Projekte angelegt sind, desto unwahrscheinlicher ist es, dass die In‐situ‐Bodenverhältnisse homogen und verfahrenstechnisch eindeutig sind. Beim maschinellen Tunnelbau im Schildvortrieb ist der Baugrund der entscheidende Faktor für die Auswahl und die Effizienz des Bauverfahrens. Eine eindeutige Differenzierung zwischen dem Einsatzbereich eines Erddruckschilds und eines Hydroschilds nur auf Grundlage der Kornverteilung des Baugrunds ist heute kaum noch möglich. Eine Verschiebung des Einsatzbereichs von Hydroschilden in den Feinkornbereich ist ebenso möglich wie die Erweiterung des Einsatzbereichs der Erddruckschilde in grobkörniges Lockergestein. In diesem Beitrag erläutern die Autoren ausgewählte geologische Situationen, die für den Einsatz von Erddruckschilden eine besondere Herausforderung darstellen können. Exemplarisch sind dies überkonsolidierte bindige Böden, stark durchlässige nichtbindige Böden sowie Sedimentfestgesteine bzw. Bereiche mit gemischter Ortsbrust aus Fest‐ und Lockergestein. Es werden Untersuchungsmethoden und Hilfsmittel für die Planung und Begleitung von Schildvortrieben vorgestellt.